Lipocalin‐2 as mediator of chemokine expression and granulocyte infiltration during ischemia and reperfusion. (23rd May 2013) - Sickinger, Stephan; Maier, Herbert; König, Stefan; Vallant, Natalie; Kofler, Markus; Schumpp, Philipp; Schwelberger, Hubert; Hermann, Martin; Obrist, Peter; Schneeberger, Stefan; Margreiter, Raimund; Troppmair, Jakob; et al.
Summary Lipocalin‐2 (Lcn2) expression contributes to ischemia and reperfusion injury (IRI) by enhancing pro‐inflammatory responses. The aim of this work was to elucidate the regulation of Lcn2 during hypoxia and its effects on the expression of key chemokines and adhesion molecules. Lcn2 wt and Lcn2−/− mice were used in a heterotopic heart transplantation model. Quantitative RT‐PCR was applied for chemokine gene expression analysis. Reporter gene studies were used to elucidate the regulation of the Lcn2 promoter by hypoxia. HIF‐1β expression led to a 2.4‐fold induction of the Lcn2 promoter. Apart from an earlier onset of granulocyte infiltration in the Lcn2 wt setting after 2 h of reperfusion compared with the Lcn2−/− setting (P < 0.013), exogenous application of recombinant Lcn2 revealed a trend toward increase of granulocyte infiltration. Analyzed chemokines were expressed significantly higher in the Lcn2 wt setting at 2 h of reperfusion (P ≤ 0.05). The number of apoptotic cells observed in Lcn2−/− grafts was significantly higher than in the Lcn2 wt setting. Our results indicate that Lcn2 affects granulocyte infiltration in the reperfused graft by modulating the expression of chemokines, their receptors and the apoptotic rate.